Sustainability Indicators Of Land-use Planning For Medium-sized Cities: A Case Study Of Nigde, Turkey - Akbulut, A; Ozcevik, O (WIT Transactions on Ecology and the Environment, 2015)
In this paper, sustainable development, proposed as a global objective, was studied with the determination of optimal city size, using a medium-sized city to achieve this. Land-use planning, managed by local governments, can be the most effective tool for the planning of medium-sized cities. In light of this information, the aim of this study is to examine the importance of having an awareness degree about the subject of local governments, for providing the measurability and applicability of sustainable development indicators by way of land-use planning. Our hypothesis is that the medium-sized cities' land-use plans can create progress related to the local goverments' knowledge, perceptions and expectations about sustainable development indicators. The case study area, Nigde City Centre, is a medium-sized city with a population of approximately 110,000 people and is located in the historical Cappadocia territory of the Central Anatolia Region of Turkey. In the first phase of the study, the current upper scale plans were evaluated by connecting them to the sustainable development indicators for Nigde. In the second phase of the study, local government authorities' knowledge, perceptions and expectations about sustainable development in land-use planning were measured by the semi-structured in-depth interview method. According to the findings of the research, Nigde has inadequate access to sustainable development indicators of land-use plans. And this inadequacy is seen at the city's local authorities' level of perception, knowledge and expectations about sustainable development indicators.